Optimalisasi Personal Branding Dosen dan Alumni dalam Pembentukan Brand Awareness Universitas Melalui Platform Digital - Yusran Efendi; Jamal Ismail (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the digital era, the personal branding of lecturers and alumni plays a strategic role in enhancing university brand awareness. A strong academic identity and a positive image presented through digital platforms can strengthen the reputation of higher education institutions. This study aims to analyze how optimizing the personal branding of lecturers and alumni contributes to shaping university brand awareness. The research method used is a literature review by analyzing various scientific sources related to personal branding, brand awareness, and digital marketing strategies in the context of higher education. Data were collected from academic journals, books, and relevant publications discussing the role of digital media in building the image of academic institutions.The findings indicate that consistent and authentic personal branding of lecturers and alumni on digital platforms such as social media, university websites, and professional networks can enhance university exposure and appeal to prospective students and other stakeholders. Active interaction, expertise-based content, and participation in online academic discussions are key factors in building credibility and public trust. The implications of this study provide insights for universities in designing effective digital branding strategies by leveraging the active role of lecturers and alumni. Universities should encourage the strengthening of personal branding through training programs and structured digital communication policies to enhance institutional competitiveness at both national and global levels.